2012
DOI: 10.12659/ajcr.882588
|View full text |Cite
|
Sign up to set email alerts
|

Pantoea species sepsis associated with sickle cell crisis in a pregnant woman with a history of pica

Abstract: SummaryBackground:Bacteria in the Pantoea genus are plant and soil associated Gram-negative rods described as nosocomial pathogens and as rare causes of community-acquired infections. The latter have been classically associated with gardening and plant thorn injuries and immunocompromised states are additional risk factors. We report a patient with pica and geophagia, Pantoea sepsis, and sickle cell crisis, associations not previously described.Case Report:A 23-year-old pregnant female presented to the emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the previously reported cases of patients with SCD infected with Pantoea [14][15][16], the possibility of gut translocation of the bacteria was raised, as one of the three reported cases was of a pregnant lady with SCD having a history of long-standing geophagia (i.e., potting soil consumption). The second case was of a child with a history of soil ingestion who was found to have Pantoea bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previously reported cases of patients with SCD infected with Pantoea [14][15][16], the possibility of gut translocation of the bacteria was raised, as one of the three reported cases was of a pregnant lady with SCD having a history of long-standing geophagia (i.e., potting soil consumption). The second case was of a child with a history of soil ingestion who was found to have Pantoea bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Through a review of the literature, we found that the incidence of Pantoea infection in patients with SCD has only been reported three times [15][16][17]. Therefore, this is the fourth report of a patient with SCD who was found positive for Pantoea spp.…”
Section: Introductionmentioning
confidence: 86%
“…Klebsiella pneumonia and Staphylococcus aureus are two other bacteria that can cause bacteremia and septicemia [66]. Salmonella species and Pantoea agglomerans enteric Gram-negative bacteria also negatively impact SCD patients [67,68]. An extensive data analysis of 550 SCD patients shows that the use of catheters during red cell exchange/transfusion increased the risk of bacteremia or thrombosis [69].…”
Section: Infectious Complications Associated With Scdmentioning
confidence: 99%
“…In recent years, sepsis incidence has been rising due to the growing elderly population, prolonged hospitalization, and increasingly aggressive medical procedures; thus, sepsis is causing a significant epidemiological and public health concern [ 3 ]. Nosocomial infectious diseases resulting from contaminated blood products, intravenous fluid, and medications have been reported [ 4 ]. The sepsis mortality rates vary from 12.8% (sepsis) and 20.7% (severe sepsis) to 45.7% (septic shock) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%